Current psychopathology models emphasize very early intersubjectivity-based interventions in children to prevent later mental disorders - Ouss, Lisa (Frontiers in Psychology, 2024)
Current psychopathology models have evolved towards dimensional models, in which symptoms and diseases are at the extremes of dimensions. Despite these new dimensional proposals, classifications and third-person approach have shown limitations. Their extraordinary evolution nevertheless underlines the contributions of developmental and psychodynamic frameworks. Developmental contributions have made it possible to evolve from disorders centered on a first-person perspective. Complementarily to the first-person/third-person perspectives, we advocate a second-person perspective, based on intersubjectivity. This perspective reverses the intuitive trend to focus our interventions on the most specific symptoms and syndromes, and advocates instead interventions on a “p” general factor that are both generalized and highly targeted. The implications are 1) to intervene as early as possible, 2) to base the definition of our therapeutic targets on an intersubjective perspective, 3) to identify and enhance children’s and parents’ strengths. These empirically informed directions are not in the current mainstream of psychopathology frameworks, and need to be developed.